Photocatalytic Properties of Tin Oxide and Antimony-Doped Tin Oxide Nanoparticles - J. C. M. Brokken-Zijp; O. L. J. van Asselen; W. E. Kleinjan; R. van de Belt; G. de With (Journal of Nanotechnology)
For the first time it is shown that N-doped SnO2 nanoparticles photocatalyze directly the polymerization of the C=C bonds of (meth)acrylates under visible light illumination. These radical polymerizations also occur when these particles are doped with Sb and when the surfaces of these particles are grafted with methacrylate (MPS) groups. During irradiation with visible or UV light the position and/or intensity of the plasmon band absorption of these nanoparticles are always changed, suggesting that the polymerization starts by the transfer of an electron from the conduction band of the particle to the (meth)acrylate C=C bond. By using illumination wavelengths with a very narrow band width we determined the influence of the incident wavelength of light, the Sb- and N-doping, and the methacrylate (MPS) surface grafting on the quantum efficiencies for the initiating radical formation (Φ) and on the polymer and particle network formation. The results are explained by describing the effects of Sb-doping, N-doping, and/or methacrylate surface grafting on the band gaps, energy level distributions, and surface group reactivities of these nanoparticles. N-doped (MPS grafted) SnO2 (Sb ≥ 0%) nanoparticles are new attractive photocatalysts under visible as well as UV illumination.